Cultura empreendedora e inspiração no mercado publicitário: processos comunicacionais nos modelos de negócios inovadores - Silva, Lina Maria Moreira Garai da (2021)
This thesis seeks to understand the discursive construction of advertising business as an innovative activity, which breaks with the tradition of the sector and is associated with the entrepreneurial culture of our time. We start from the assumpt ion that innovation is treated as an inspirational element (CASAQUI, 2017) impregnated with senses of neoliberal culture (DARDOT; LAVAL, 2016), to reconfigure the social imaginary of entrepreneurial advertisers, supposedly more adapted to the spirit of our time (BOLTANSKI; CHIAPELLO, 2009). We rely on the theoretical methodological perspective of the social discourse of the “hegemony of the thinkable” approach (ANGENOT, 2010) to analyze the corpus made up of images photos posted on the social media of adver tising businesses, entrepreneurs and news about them published in media publications advertising. The results point to evidence of a strategy to survive the crisis in the advertising sector based on discursive arrangements structured based on symbolic reso urces of technological culture as a networked work community, flexible working environment, subjectivity management as inspirational elements that contribute to the elaboration of the perception of the new.(AU)